Tlingit women in canoes with coastal town in background, Alaska, between 1898 and 1900 - Hester, Wilhelm, 1872-1947 (1898)
One of the buildings may be a cannery. PH Coll 318.1093 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number